LINGUISTIC AND CULTURAL CHARACTERISTICS OF TONGUE TWISTERS: A LITERATURE REVIEW - Surmilova, Elena (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The article looks at the history of the research done around tongue-twisters from the linguistic and cultural points of view. Phonological, stylistic and syntactic features that contribute to the complexity of tongue-twisters has been explored. Additionally, the review ehamines the significance of tongue-twisters as the way of linguistic reflection of culture.